Existing opportunities to increase the effectiveness of tuberculosis Treatment - Y.I. Feshchenko; M.I. Gumeniuk; O.Ya. Korolyuk (Civic Union "Communicable Diseases Intensive Care Association", 2018)
INTRODUCTION. According to the WHO, tuberculosis remains one of the 10 leading causes of death in the world. Certain features of the pathogen, peculiarities of treatment regimens and some individual characteristics of patients create barriers to the effective treatment of the disease. MATERIALS AND METHODS. Retrospective analysis of literary sources - recommendations, scientific articles and statistical data. RESULTS. A review of the literature data showed features of the pathogen, patient-related problems and possible omissions in treatment regimens, that may be the cause of treatment effectiveness lack and a risk factor for the emergence of drug resistance in M. tuberculosis. Insufficient efficacy of treatment was described in patients with low adherence to treatment with oral anti-TB drugs, the presence of comorbidities, with a low level of intestinal permeability of oral medications and in patients with severe forms of tuberculosis. All these patients had a high mortality rate when treated within standard regimens using oral medications. CONCLUSIONS. To solve the problems of low TB treatment efficiency in these categories of patients, the necessary measures are aimed at maximizing the elimination of causes listed in the article in order to optimize treatment regimens in accordance with the patient's characteristics and needs, taking into account the peculiarities of mycobacteria.